THE IMPACT OF TECHNOLOGY ON MORAL EDUCATION IN THE DIGITAL AGE - Indah Fajar Wahyuni (Global Synthesis in Education Journal, 2025)
Reading is a central component of English as a Foreign Language (EFL) literacy development. On the other hand Indonesian young learners consistently experience difficulties in vocabulary recognition, sentence comprehension, identifying main ideas, and maintaining reading motivation. This study explores fifth-grade students’ reading difficulties and uses these findings as the foundation for developing digital comic-strip learning media. Employing a qualitative descriptive approach integrated into the analysis phase of the ADDIE model, data were collected through classroom observations, teacher interviews, student questionnaires, and curriculum analysis. Thematic analysis revealed four dominant reading challenges: limited vocabulary mastery, difficulty identifying main ideas, low motivation toward reading, and challenges in understanding English grammatical structures. These insights informed the design of six digital comic-strip learning media, which were then evaluated for feasibility. Media experts rated the product at 80% and material experts at 88.89%, indicating high feasibility. Student responses (77.83%) demonstrated strong acceptance of the media, highlighting visuals and content clarity as major strengths. These findings align with both Indonesian and international studies confirming the effectiveness of multimodal learning media—especially digital comics—in supporting comprehension, enhancing vocabulary recognition, and increasing motivation. The study concludes that digital comic strips represent a responsive and pedagogically sound medium for addressing young learners’ reading difficulties. Recommendations are offered for broader implementation and further development of digital comic-based instructional tools